2019
DOI: 10.1371/journal.pone.0216199
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and preventive practices of primary health care professionals towards alcohol use: A national, cross-sectional study

Abstract: Introduction Primary care (PC) professionals' knowledge about alcohol use has been identified as one of the barriers PC providers face in their clinic. Both PC professionals’ level of training and attitude are crucial in the clinical practice regarding alcohol use. Objective To evaluate the knowledge, attitude, and preventive practices of Spanish PC physicians and nurses towards alcohol use. Design An observational, descriptive, cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
1
9
1
1
Order By: Relevance
“…In contrast to earlier studies implicating quite low levels of alcohol-related knowledge among health care personnel [ 49 54 ], OHS personnel in our study believed that they were quite knowledgeable about alcohol-related topics. Evidence of limited knowledge among health care personnel has been found regarding topics such as effects of alcohol consumption on health [ 52 ], prevalence of alcohol use and risky drinking [ 49 , 53 ], etiology of alcoholism [ 54 ], fetal alcohol spectrum disorders and maternal alcohol use [ 50 – 52 ], drinking limits, guidelines and how to advise patients about responsible drinking [ 55 , 56 ], how to screen for substance misuse [ 59 ], and effectiveness of brief alcohol interventions [ 53 , 54 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to earlier studies implicating quite low levels of alcohol-related knowledge among health care personnel [ 49 54 ], OHS personnel in our study believed that they were quite knowledgeable about alcohol-related topics. Evidence of limited knowledge among health care personnel has been found regarding topics such as effects of alcohol consumption on health [ 52 ], prevalence of alcohol use and risky drinking [ 49 , 53 ], etiology of alcoholism [ 54 ], fetal alcohol spectrum disorders and maternal alcohol use [ 50 – 52 ], drinking limits, guidelines and how to advise patients about responsible drinking [ 55 , 56 ], how to screen for substance misuse [ 59 ], and effectiveness of brief alcohol interventions [ 53 , 54 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Health care personnel’s level of alcohol training has been found to predict the extent to which they actually treat individuals with alcohol-related problems [ 48 ]. Although results are somewhat inconsistent, studies suggest that health care personnel have quite a low level of alcohol-related knowledge [ 49 54 ]. Similar findings have been reported for students in health professions [ 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results show that midwives and nurses were significantly more likely to lack knowledge on the recommended daily salt intake than medical doctors were, although significant differences were not found between medical doctors and public health nurses. This finding is similar to that from a previous study that revealed health care professionals’ knowledge regarding alcohol consumption differed significantly depending on the type of occupation [ 16 ]. The reason significant differences were not found between medical doctors and public health nurses might be due to the small sample size of public health nurses or because the role of public health nurses is to give health guidance to the community; in addition, some of the nurses were not specialists in public health or cardiovascular internal medicine.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, it is observed that professionals with more training are more likely to counsel their patients to reduce or abstain from alcohol use, particularly in cases of pregnant women and motor vehicle drivers. Given the importance of this finding in the clinical setting, strengthening the training of health professionals in this area should be a priority [ 38 ], in order to improve levels of prevention and health promotion, especially in at-risk populations, such as adolescents [ 39 ], pregnant women [ 40 ], and those whose alcohol consumption may have repercussions on third parties, such as operators of machinery and motor vehicle drivers [ 41 ].…”
Section: Discussionmentioning
confidence: 99%